Level of physical activity in women with breast cancer who conducted combined training - Coelho, Rafael dos Santos; Reis, Andréa Dias [UNESP] (Desafio Singular, Lda, 2018)
Introduction. The prevalence of patients with breast cancer grows alarmingly and side effects of treatment influence the functional capacity of patients. Goal. To evaluate the influence of combined training (CT) on labor activity, level of physical activity and adverse effects. Methods. Pilot controlled study with 28 patients in patients undergoing breast cancer treatment (30 to 59 years), being allocated in Experimental Group (EG), where they performed the CT (aerobic+resistance and flexibility) in 12 weeks and the control group (CG) did not perform CT. Results. The EG patients showed an increase in the level of physical activity (p=0.0086), different from the CG not had a significant difference (p=0.1573). Adverse effects showed significant differences (p=0.0056) between the groups after 12 weeks of physical training, unlike the labor activity that showed no significant difference (p=0.065). Conclusion. The physical training was effective to increase the level of physical activity in patients with breast cancer.
Nível de atividade física em mulheres com câncer de mama que realizaram treinamento combinado
Keywords: Breast neoplasms; Disease; Exercise